LATITUDINAL ACTIVATION OF MAGMATISM AS A RESPONSE TO CYCLIC TIDAL EVOLUTION IN THE EARTH-MOON-SUN SYSTEM - Avsyuk Yu.N.; Saltykovsky A.Ya.; Genshaft Yu.S. (My University, 2007)
The oscillatory, cyclic tidal evolution of the Earth–Moon system influences the stress state of the lithosphere. The periodicity of the tidal evolution is close to the periodicity of Bertrand cycles, while the time intervals between peak deformations of the lithosphere 40–60 Ma ago correspond to Stille cycles. This regime was revealed during investigation of solar disturbances of the Earth’s orbital motion around the Earth–Moon center of mass.